Quantitative Cross-country Analysis of Nuclear Power Discourse in Politically Distinct India and Russia. (September 2021) - Sharonova, Yelizaveta Mikhailovna
Nuclear power has always been a controversial issue since it was discovered as a source of power for civil use. Despite being a global phenomenon, nuclear power is viewed differently around the world, and consequently, different discourses have had different outcomes. This study does a comparative analysis of nuclear power discourses between India and Russia, two countries of distinct political systems. This study analyses the media coverage and content of the main discourse themes in India's and Russia's print media from March 2011 to March 2019. The study finds that in both countries, despite their different political set-ups, nuclear power discourse has a pro-nuclear character.